1998
DOI: 10.1038/2934
|View full text |Cite
|
Sign up to set email alerts
|

A novel DNA-binding motif shares structural homology to DNA replication and repair nucleases and polymerases

Abstract: A novel class of DNA-binding domains has been established from at least sixteen recently identified DNA-binding proteins. The three-dimensional structure of one of these domains, Mrf-2, has been solved using NMR methods. This structure is significantly different from known DNA-binding domain structures. The mechanism of DNA recognition by this motif has been suggested based on conserved residues, surface electrostatic potentials and chemical shift changes. This new DNA-binding motif shares structural homology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 33 publications
1
53
2
Order By: Relevance
“…It has previously been reported that the structure formed by O, O1, and O2 helices of pol I shares structural homology with a novel DNA binding motif (24) found in transcription factor Mrf-2 and in some DNA repair proteins such as E. coli endonuclease III (25) and T4 RNase H (24,26). This structural homology suggested the involvement of this motif in the recognition of double-stranded nucleic acid.…”
Section: Properties Of Sermentioning
confidence: 91%
See 1 more Smart Citation
“…It has previously been reported that the structure formed by O, O1, and O2 helices of pol I shares structural homology with a novel DNA binding motif (24) found in transcription factor Mrf-2 and in some DNA repair proteins such as E. coli endonuclease III (25) and T4 RNase H (24,26). This structural homology suggested the involvement of this motif in the recognition of double-stranded nucleic acid.…”
Section: Properties Of Sermentioning
confidence: 91%
“…This structural homology suggested the involvement of this motif in the recognition of double-stranded nucleic acid. However, for the DNA polymerase I family of enzymes, it was suggested that this region may be important in the binding of the ssDNA template overhang (24).…”
Section: Properties Of Sermentioning
confidence: 99%
“…Although these ARID domains are conserved from humans to yeast, their DNA-binding specificities may not be conserved. The solution structures of two different ARID domains have recently been reported (24,49).…”
Section: Discussionmentioning
confidence: 99%
“…It was identified in our laboratory in 1996 as a novel nuclear protein that binds to sequences upstream of the human cytomegalovirus major immediate-early enhancer/promoter and exerts repressor activity in undifferentiated human Tera-2 cells (1). Subsequent studies revealed the three-dimensional structure of the novel DNA-binding motif (ARID) of Mrf-2 and mechanisms of DNA recognition (2)(3)(4). The ARID family of DNA-binding proteins has grown since then to include fifteen proteins found in humans and most other vertebrate species, and six proteins found in Drosophila as well as proteins found in worms, fungi, plants and yeast (5)(6)(7)(8).…”
Section: Arid5b (At-rich Interaction Domain-containingmentioning
confidence: 99%